School chair design and key criteria from the users’ point of view - Rizman Herga, Nataša; Fošnarič, Samo; Kolar, Andreja (Annales Kinesiologiae, 2020)
People are becoming increasingly sedentary, including students attending the upper level of primary education. Due to school, young people spend a lot of time sitting in class and at home, which has a negative effect on their health, especially if their work environment, including school furniture, does not meet all the criteria in terms of physiological, psychological, and sociological guidelines for healthy furniture design. Chairs, as school furniture, have been designed according to standards that take into account ergonomic compliance with the body height of pupils. Slovenian classrooms are equipped with standard conventional chairs. In our student-oriented research, we were interested in whether chairs designed according to the standard are suitable for adolescents and what, if any, additional criteria must be met from the users’ point of view. The study included 192 upper level pupils (56.3 % girls and 43.7 % boys), age of 12.4 ± 1.7 years. The research is based on quantitative and qualitative methodology. The descriptive causal non-experimental method was supported by the observation method. The results of the survey show that older students (81.6 %) are of the opinion that they spend more time at school than at home. Due to prolonged sitting, older students (55.3 %) report problems more often than younger ones (28.4 %). Nearly two-thirds of younger students (63.8 %) also believe they sit more in school than at home. The results show that prolonged sitting negatively affects their health or general well-being. Differences between the responses of older and younger pupils are statistically significant both in the opinion expressed regarding the location of sitting (p = 0.010) and in the reporting of problems due to prolonged sitting (p = 0.001). There are no statistically significant differences between the sexes in both groups of older and younger pupils. Pupils sit on hard, uncomfortable, conventional chairs that are not tailored to their needs. They want to use comfortable, soft, swivel chairs with backrests and armrests. The study has shown that, in addition to comfort, school chairs must provide dynamic or active sitting. The present study confirms that static and rigidly shaped school chairs do not offer support for active and restless youth. Therefore, chair design must change to meet the physical, ergonomic, cognitive, and social needs of their users.